The use of 6-0 glycomer 631 for perineal urethrostomy in male cats: 314 cases (2013–2023) - Hankins, Kimery; Zacher-Coy, Laurie (Frontiers in Veterinary Science, 2025)
ObjectiveTo assess the prevalence of postoperative complications in cats that underwent perineal urethrostomy (PU) in which 6-0 glycomer 631 was used to suture urethral mucosa to skin.Animals314 male cats.ProceduresMedical records for cats that received a PU at Central Texas Veterinary Specialty & Emergency Hospital between 2013 and 2023 were assessed. Details including signalment, clinical status, additional surgical procedures, and postoperative complications were recorded.Results18 of 314 (5.7%) cats developed minor complications, and 7 of 314 (2.2%) cats developed major complications that required surgical revision or resulted in humane euthanasia.Clinical relevanceUsing 6-0 glycomer 631 suture is acceptable for apposition of urethral mucosa to skin in cats that undergo PU. Minor complication rates were lower and percentage of cats requiring revision surgery comparable to values reported in previous studies in which absorbable, nonabsorbable, or larger suture types were used.